Inward-to-outward assembly of amine-functionalized carbon dots and polydopamine to Shewanella oneidensis MR-1 for high-efficiency, microbial-photoreduction of Cr(VI). (November 2022) - Li, Jian; Wang, Feng; Zhang, Jing; Wang, Honghui; Zhao, Chongyuan; Shu, Lielin; Huang, Peng; Xu, Yejing; Yan, Zhiying; Dahlgren, Randy A.; Chen, Zheng
Abstract: A novel photosensitized living biohybrid was fabricated by inward-to-outward assembly of amine-functionalized carbon dots (NCDs) and polydopamine (PDA) to Shewanella oneidensis MR-1 and applied for high-efficiency, microbial-photoreduction of Cr(VI). Within a 72 h test period, biohybrids achieved a pronounced catalytic reduction capacity (100%) for 100 mg/L Cr(VI) under visible illumination, greatly surpassing the poor capacity (only 2.5%) displayed by the wild strain under dark conditions. Modular configurations of NCDs and PDA afforded biohybrids with a large electron flux by harvesting extracellular photoelectrons generated from illuminated NCDs and increasing reducing equivalents released from an enlarged intracellular NADH/NAD + pool. Further, increased production of intracellular c-type cytochromes and extracellular flavins resulting from the modular configuration enhanced the biohybrid electron transport ability. The enhancement of electron transport was also attributed to more conductive conduits at NCDs-PDA junction interfaces. Moreover, because NCDs are highly reductive, the enhanced Cr(VI) reduction was also attributed to direct reduction by the NCDs and the direct Cr(VI) reduction by sterile NCDs-assembled biohybrid was up to 20% in the dark. Overall, a highly efficient strategy for removal/transformation of Cr(VI) by using NCD-assembled photosensitized biohybrids was proposed in this work, which greatly exceeded the performance of Cr(VI)-remediation strategies based on conventional microbial technologies. Graphical abstract: Image 1 Highlights: A novel photosensitized biohybrid was fabricated using inward-to-outward assembly of NCDs and PDA to S. oneidensis MR-1. Biohybrids enhance the bulk electron flux by harvesting reducing equivalents and photoelectrons and reducing powers. Increased interfacial conductivity ensures rapid intracellular/extracellular charge transport in biohybrids. Biohybrids withstand high Cr(VI) exposure and achieve highly efficient microbial-photoreduction of Cr(VI).